Penerapan Algoritma Entropy Dan Aras Menentukan Penerima Beasiswa Mahasiswa Berprestasi Di Pemerintah Kabupaten Labuhanbatu - Andi Ernawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In handling scholarship data for outstanding students, the Labuhanbatu Regency government in general still uses manual recording, namely by using a ledger and there is no computerization in determining the receipt of scholarships for outstanding students, so there are many mistakes in determining it. The problem faced by the many recipients of scholarships for outstanding students who are not appropriate so that those who deserve to receive do not receive and those who do not deserve to receive scholarships. This problem occurs because of the difficulty in implementing the selection of scholarship recipients due to the large number of applicants and the number of the same criteria in receiving scholarships. So that mistakes often occur To apply for a scholarship at the People's Welfare Office in the Labuhanbatu Regency government, students must fill out a form containing data from the student, such as Grade Point Average (GPA), Parents' income, Number of Siblings, Number of Dependent Parents. The ranking process in receiving scholarships uses the Entropy Method in giving weighting to the criteria objectively and the ARAS Method, which is a suitable method in determining the calculation of weights based on predetermined criteria and ranking from a set of alternative data that kick each other. So that it can reduce the errors that have been faced so far.